NICU Room Baby Care at the Sekarwangi Regional General Hospital: Mothers’ Satisfaction with Baby Care and Social Support for Mothers with Premature Infants - Lisbet Octovia Manalu; M. Iqbal Sutisna (STIKep PPNI Jawa Barat, 2022)
Aims: The hospitalization and inpatient experiences of premature babies in hospitals cause high levels of anxiety and symptoms of depression in parents, loss of confidence in caring for babies, and being overprotective for children. Premature birth and low birth weight (LBW) babies are still relatively common in Indonesia. The baby, as well as developmental and behavioral retardation problems. Pediatric nurses in providing interventions, have a role in facilitating parents to provide bonding attachments and optimizing Family Centered-Care (FCC). Objective: To determine the social support and satisfaction of mothers of premature babies with care in the NICU room at Sekarwangi Hospital. Methods: The Social Support Questionnaire and the Neonatal Instrument of Parent Satisfaction (NIPS) Questionnaire was adjusted used in this cross-sectional survey. Non-probability sampling as well as consecutive sampling are indeed methods of sampling. The Chi-Square Test was used to check. Results: Mothers' satisfaction with infant care in the NICU room is satisfying, that as 44 respondents (88 percent), and social support for mothers of premature babies receiving care there is good, according to 47 respondents (94 percent). Conclusion: Social support for mothers of premature newborns and mothers' satisfaction with the care of the infants in the NICU Room at the Sekarwangi Regional General Hospital are associated.